L’impact de la Révolution française sur l’évolution du concept de révolution en Chine (fin XIXe-début XXe siècle) - Céline Wang (Astérion)
The French Revolution, and certain ideas of the Enlightenment, produced a radical change in the meaning of the term geming (revolution) that, becoming a slogan, spawned a new current of thought at the end of the Qing Dynasty. Known belatedly in China, it was first presented as a negative term to preach urgent political reform, then became the subject of polemical debate between reformers and revolutionaries. At the same time, the term geming, which originally referred to "change of heavenly mandate", never ceased to provoke various interpretations depending on the period and the political position of the commentators. The objective of this article is to question the process of transformation of this notion and its adaptation to Chinese reality, in order to better measure what constitutes the legacy of the French Revolution in the construction of modern China.